The importance of social support and coercion to risk of impulsivity and juvenile offending - Kurtz, Don L. (Crime & delinquency, 2017)
The current study provides a comprehensive test of differential social support and coercion (DSSC) theory of crime as proposed by Colvin, Cullen, and Vander Ven. DSSC suggests that social interactions are either coercive or supportive in nature and that these interactions figure prominently into the development of self-control and delinquent behavior. Data drawn from the Evaluation of the Gang Resistance Education and Training (GREAT) assess four DSSC research hypotheses. Ordinary least squares (OLS) regression suggests that parental support reduces impulsive behavior whereas coercive relationships correlate with increased impulsivity. Logistic regression indicates that parental support associates with reduced violent offending odds and that interpersonal coercion and low self-control increase violent offending. Beyond testing micro-level DSSC theory, these findings have important implications for criminal justice responses to juvenile offending.